Faktor-Faktor yang Berhubungan dengan Upaya Pencegahan Penyebaran COVID-19 pada Penderita Hipertensi - Mila Sartika; Armi Armi (Journal of Telenursing (JOTING), 2022)
This study aims to analyze efforts to prevent the spread of COVID-19 in patients with hypertension in Mangunjaya Village, Bekasi Regency, in 2020. The method used is the survey method. The results showed a relationship between wearing masks, keeping a distance, maintaining immunity and controlling comorbidities with the spread of COVID-19 in patients with hypertension, while there was no relationship between WFH and the spread of COVID-19. Hand washing activity is the dominant variable in preventing the spread of COVID-19, with an OR value of 9.111. In conclusion, the need for efforts to maintain health by adhering to implementing health procedures, increasing immunity and controlling comorbidities by actively controlling blood pressure and remaining consistent in implementing a low-salt diet to maintain blood pressure stability. Keywords: COVID-19, Hypertension, Comorbid, Hand Washing